Microstructure and mechanical properties of Ni1, 5Co1, 5CrFeTi0, 5 high entropy alloy fabricated by mechanical alloying and spark plasma sintering. (5th April 2017) - Moravcik, Igor; Cizek, Jan; Zapletal, Jozef; Kovacova, Zuzana; Vesely, Jozef; Minarik, Peter; Kitzmantel, Michael; Neubauer, Erich; Dlouhy, Ivo
Abstract: The present work is focused on synthesis and mechanical properties evaluation of non-equiatomic Ni1, 5 Co1, 5 CrFeTi0, 5, ductile single phase high entropy alloy (HEA) with excellent mechanical properties (bend strength R mb = 2593 MPa, tensile strength R m = 1384 MPa, tensile elongation to fracture of 4.01%, and elastic modulus of 216 GPa) surpassing those of traditional as-cast HEA. For the alloy production, a combination of mechanical alloying (MA) process in a planetary ball mill and spark plasma sintering (SPS) for powder densification was utilized. The tensile properties of a bulk material produced by a combination of MA + SPS are characterized for the first time. The feedstock powder and corresponding bulk material microstructure, elemental and phase composition, and mechanical properties were investigated by scanning (SEM) and transmission (TEM) electron microscopy, energy-dispersive X-ray spectroscopy (EDX), electron backscatter diffraction (EBSD), X-ray diffraction (XRD), as well as impulse excitation of vibration, Vickers microhardness and tensile and bend strength tests, respectively. The structure of the samples consisted of single-phase FCC high entropy solid solution of extremely fine-twinned grains and oxide inclusions inherited from the original powder feedstock. Dimple-like morphology corresponding to ductile fracture mode has been observed on the fracture surfaces, with crack initiation sites on the inclusions phases. Graphical abstract: Highlights: One phase FCC ultra-fine grained HEA with no porosity was produced via powder metallurgy. For the first time, tensile test specimens produced from SPS compacts were tested. The alloy exhibited excellent tensile strength of 1384 MPa, superior to HEA produced by casting routes. Ductile fracture mode with dimple morphology has been observed on fracture surfaces.